2020
DOI: 10.1080/0886022x.2020.1822185
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia, the heart, and the kidneys – to treat or not to treat?

Abstract: Background: Hyperuricemia is a state in which the serum levels of uric acid are elevated. As such it has a pronounced effect on vascular and renal function with their consequences, while also showing some antioxidant effects that show to be beneficial. Summary: Hyperuricemia has shown to have a J-shaped relationship with mortality, is frequently associated with development and progression of heart and kidney disease, and is correlated with malnutrition-inflammation-atherosclerosis syndrome, although several Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 94 publications
1
29
0
1
Order By: Relevance
“…Hyperuricemia is defined as a UA concentration higher than 7 mg/dL in men, 6 mg/dL in women, and 5.5 mg/dL in children and teenagers [ 24 ]. Causes of hyperuricemia are rich purine diets, congenital disorders, tumor lysis syndrome, seizures, rhabdomyolysis [ 25 ], hypercatabolic states [ 26 ], or drugs (i.e., acid acetylsalicylic, theophylline, mycophenolate, beta- and alfa- adrenergic antagonists, angiotensin-converting enzyme, cyclosporine) [ 27 ]. Low serum level of UA may be encountered in large volumes of parenteral fluids, psychogenic polydipsia, inappropriate antidiuretic hormone (SIADH), or in some hepatic diseases (i.e., cholangiocarcinoma, viral hepatitis, primary cirrhosis), immunosuppression, or neoplasia.…”
Section: Uric Acid Synthesismentioning
confidence: 99%
“…Hyperuricemia is defined as a UA concentration higher than 7 mg/dL in men, 6 mg/dL in women, and 5.5 mg/dL in children and teenagers [ 24 ]. Causes of hyperuricemia are rich purine diets, congenital disorders, tumor lysis syndrome, seizures, rhabdomyolysis [ 25 ], hypercatabolic states [ 26 ], or drugs (i.e., acid acetylsalicylic, theophylline, mycophenolate, beta- and alfa- adrenergic antagonists, angiotensin-converting enzyme, cyclosporine) [ 27 ]. Low serum level of UA may be encountered in large volumes of parenteral fluids, psychogenic polydipsia, inappropriate antidiuretic hormone (SIADH), or in some hepatic diseases (i.e., cholangiocarcinoma, viral hepatitis, primary cirrhosis), immunosuppression, or neoplasia.…”
Section: Uric Acid Synthesismentioning
confidence: 99%
“…However, lifestyle modifications and targeted pharmacological urate-lowering therapy can be beneficial in certain sub-groups of patients and systematic identification of such patients is another big challenge for the clinicians. 25 Limitations of our study was being a single-center study and having a small sample size and limits the generalizability of study findings.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, some studies reported no effect of febuxostat on eGFR decline with asymptomatic hyperuricemia in CKD stage 3 patients [ 28 , 29 ]. In addition, recent systematic review has showed evidence that asymptomatic hyperuricemia should be treated under limited conditions: persistent SUA level higher than 13 mg/dL (men) or 10 mg/dL (women) and urinary excretion of uric acid exceeding 1,100 mg daily [ 30 , 31 ]. For individuals of asymptomatic hyperuricemia like our cohort, there have been no sufficient evidence to treat hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%